Gestión de Auditorías Internas en un Laboratorio Farmacéutico - Pintado Burgos, Laura Nataly (2018)
This report on pre-professional practices aims to develop the management of internal audits by adapting to the checklists according to the needs of the internal protocols of the sterile ophthalmic solutions manufacturing laboratory. The first corresponded to an internal audit conducted in May, and the second audit was conducted in November, which aims to verify the different procedures and internal control systems established by the pharmaceutical laboratory in order to establish whether they meet the established standards: BPM and ISO 9001. A set of activities was planned which allowed the two internal audits to be carried out satisfactorily, obtaining the following results: in the production and warehouse area, the same number of findings of non-conformities is evidenced, both in the audit 2017-I and 2017-II. In the area of Quality Control, Maintenance and Validations, it is evident that the observations found in the 2017-II audit decrease with respect to the 2017-I audit. The audits allowed us to determine the observations and based on this, the correct analysis of the root cause that allowed us to eradicate them was carried out. Therefore, it is concluded that the quality management of the pharmaceutical laboratory presents a continuous improvement, taking as an indicator the internal audits